Improving ECC Ozonesonde Data Quality: Assessment of Current Methods and Outstanding Issues. Issue 3 (15th March 2021) - Tarasick, David W.; Smit, Herman G. J.; Thompson, Anne M.; Morris, Gary A.; Witte, Jacquelyn C.; Davies, Jonathan; Nakano, Tatsumi; Van Malderen, Roeland; Stauffer, Ryan M.; Johnson, Bryan J.; Stübi, Rene; Oltmans, Samuel J.; et al.
Abstract: We review the current state of knowledge of ozonesonde uncertainty and bias, with reference to recent developments in laboratory and field experiments. In the past 20 years ozonesonde precision has improved by a factor of 2, primarily through the adoption of strict standard operating procedures. The uncertainty budget for the ozone partial pressure reading has contributions from stoichiometry, cell background current, pump efficiency and temperature, sensing solution type, and volume. Corrections to historical data for known issues may reduce biases but simultaneously introduce additional uncertainties. This paper describes a systematic approach to quantifying these uncertainties by considering the physical and chemical processes involved and attempts to place our estimates on a firm theoretical or empirical footing. New equations or tables for ozone/iodine conversion efficiency, humidity and temperature corrections to pump flow rate, and altitude‐dependent pump flow corrections are presented, as well as detailed discussion of stoichiometry and conversion efficiencies. The nature of the so‐called "background current" is considered in detail. Two other factors particularly affecting past measurements, uncertainties and biases in the pressure measurement, and the comparison of sonde profiles to spectrophotometric measurements of total column ozone, are also discussed. Several quality assurance issues remain, but are tractable problems that can be addressed with further research. This will be required if the present goal of better than 5% overall uncertainty throughout the global ozonesonde network is to be achieved. Plain Language Summary: Ozonesondes are a stable reference for the global ozone observing network, making relatively inexpensive, accurate measurements of ozone from the ground to 30 km, with high vertical resolution, for more than 50 years. Ozonesonde data are used extensively for validation of satellite ozone measurements, models, and for trend analyses. The current state of knowledge of ozonesonde uncertainty and bias is reviewed, and a systematic approach to quantifying these uncertainties by considering the physical and chemical processes involved is presented. While ozonesonde precision has improved through the adoption of strict standard operating procedures, further improvement is possible with further research, toward a goal of less than 5% overall uncertainty throughout the global network. Key Points: Review of the current state of knowledge of ozonesonde uncertainty and bias A systematic approach to quantifying these uncertainties by considering the physical and chemical processes involved Uncertainties related to stoichiometry and sensor response may be reduced with further research, toward a goal of less than 5% uncertainty in the global network